Stable functionalization of small semiconducting polymer dots via covalent cross-linking and their application for specific cellular imaging - Yu, Jiangbo (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.